PENGAMATAN AWAN CIRRUS SUBVISIBLE DI ATAS BANDUNG MENGGUNAKAN RAMAN LIDAR (STUDI KASUS: BULAN SEPTEMBER 2000) - Saipul Hamdi; Sri Kaloka (Lembaga Penerbangan dan Antariksa Nasional, 2004)
Lidar Equipment has been developed by some lidar groups, and shows good performance for monitoring vertical profile of water vapour, temperature, and aerosol. In 1996, lidar equipment has been installed in LAPAN Bandung under joint research between Indonesia and Japan, and start for intensively observation since the beginning of 1997. There are several parameters can be taken by Lidar i Bandung, i.e. vertical distribution of backscattering ratio, depolarization ratio, and temperature. Observation taken in September 17th, 2000 is simultaneously to radiosonde observation. At this time we detect the existence of optically this layerjust below tropopause. We suggest this layer as subvisible cirrus cloud. This layer is 2 km thick and temperature is in range -70℃ to -80℃. Depolarization ratio of this layer is 10% or more, and backscattering ratio is less than 3.